Cell-Based Quantification of Chronic Wasting Disease Prions - Bian, Jifeng (American Society for Microbiology (ASM), 2010)
Cell-based measurement of prion infectivity is currently restricted to experimental strains of mouse-adapted scrapie. Having isolated cell cultures with susceptibility to prions from diseased elk, we describe a modification of the scrapie cell assay allowing evaluation of prions causing chronic wasting disease, a naturally occurring transmissible spongiform encephalopathy. We compare this cervid prion cell assay to bioassays in transgenic mice, the only other existing method for quantification, and show this assay to be a relatively economical and expedient alternative that will likely facilitate studies of this important prion disease.